Trade in global food systems - Jackson, Lee Ann (2016)
Presented by Lee Ann Jackson, Counsellor, Agriculture and Commodities Division, World Trade Organization (WTO), at the Geneva Launch of IFPRI's 2016 Global Food Policy Report, April 12, 2016. More info: https://www.ifpri.org/event/geneva-launch-ifpris-2016-global-food-policy-report